Trade liberalization, employment, and gender in Ethiopia - Giorgia Giovannetti; Marco Sanfilippo; Arianna Vivoli (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
This paper analyses the impact of trade liberalization on local labour markets in Ethiopia, with a focus on the gender dimension of employment. By exploiting rich micro-level data on Ethiopian workers, we evaluate the effect of the Ethiopian trade reforms on the changes and composition of employment, adopting as unit of analysis Ethiopian districts. We find that districts more exposed to trade liberalization experienced reductions in their employment levels, especially in female employment. We also show that reductions in (agricultural) input tariffs triggers a process of sectoral reallocation from agriculture to services and that this process is particularly pronounced for women. This in turns contributes to increase sectoral segregation.
Keywords: C23; F14; F16; J16; 330; tariffs; employment; structural transformation; gender; Ethiopia